Agency and leadership by Indigenous education workers for family-school-community engagement - Johnson, Greer; Flückiger , Bev (The Australian Journal of Indigenous Education, 2022)
This paper presents a single-site case study to explicate some of the issues that relate to developing a genuine and successful role for Indigenous education workers (IEWs) especially those who reside in remote Australian communities. It draws attention to the lost opportunities for agency and leadership in culturally relevant literacy teaching with families, schools and community. The study employs a social justice framework to explore a theory of intended change resultant from the inclusion of IEWs in a professional learning coalition of school leaders, teachers, and Indigenous elders with university researchers throughout an 18-month project. This evidence of intended change focuses on the IEWs’ display of agency in leading families and community in the production of culturally relevant story texts to support children’s reading inside and outside school. The paper contributes to a scant body of literature highlighting the valuable work conducted by IEWs, and justifies more meaningful employment and formal leadership roles in schools and in the community. This work lays the foundation for further research involving IEWs’ leadership in producing culturally relevant criteria for measuring change in children’s literacy outcomes and change in family-community engagement in children’s reading.